IDNLearn.com: Where curiosity meets clarity and questions find their answers. Discover comprehensive answers to your questions from our community of experienced professionals.
Sagot :
Answer:
x should equal three
Step-by-step explanation:
5(x + 1) - 8 = 5x(2 - 4)
5x+1-8=5x-4
5x-7=5x-4
+7 +7
5x= 5x +3
÷ 5 ÷5
×=3
5(x + 1) - 8 = 5x(2-4)
5x + 5 - 8 = 10x - 20x
5x - 3 = -10x
= 5x - 5x - 3 = -10x - 5x
= -3 = -15x
= -3/-15 = -15x/-15
= 0.2 = X
So, in conclusion, X is equal to 0.2
5x + 5 - 8 = 10x - 20x
5x - 3 = -10x
= 5x - 5x - 3 = -10x - 5x
= -3 = -15x
= -3/-15 = -15x/-15
= 0.2 = X
So, in conclusion, X is equal to 0.2
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.